Fingolimod for the treatment of Relapsing-Remitting Multiple Sclerosis: an overview of systematic reviews - de Mendonça Lima, Tacio; Felicissimo Gomes de Souza Bandeira, Tayna; Manso de Mello Vianna, Cid; Bittencourt Gonzalez Mosegui, Gabriela (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Objective: This overview aimed to summarize the evidence of efficacy and safety of fin-golimod in the treatment of Relapsing Remitting Multiple Sclerosis (RRMS). Method: A literature search was performed in Medline, the Cochrane Library, EMBASE, and LILACS on 18 February 2025. We included systematic reviews with meta-analyses on the use of fingolimod compared to other treatments in adults with low or moderate activity RRMS. Two authors performed study selection, data extraction, and quality assessment using Rayyan QCRI, AMSTAR-2, and GRADE tools. Three studies were included. Results: Re-garding efficacy, two reviews showed that fingolimod significantly reduced the annualized relapse rate (by 26% to 48%), and one indicated a reduction of approximately 35% in relapses over 24 months. For disability progression at 24 months, no relevant difference was observed between fingolimod and comparators. Regarding safety profile, one review reported that serious adverse events were similar between fingolimod and most com-parators, except for interferon β-1a. The methodological quality of the reviews ranged from “critically low” to “high”, and the quality of the evidence ranged from “very low” to “moderate”. Conclusion: Fingolimod demonstrated superiority over glatiramer acetate, interferons β-1a and β-1b, and teriflunomide in reducing the relapse rate, but not in preventing disability progression. Despite the favorable results, these findings should be interpreted cautiously, as the efficacy data come from short-term clinical trials and do not reflect long-term effectiveness throughout RRMS.